FBXO43 variants in patients with female infertility characterized by early embryonic arrest. Issue 8 (30th May 2021) - Wang, Weijie; Wang, Wenjing; Xu, Yao; Shi, Juanzi; Fu, Jing; Chen, Biaobang; Mu, Jian; Zhang, Zhihua; Zhao, Lin; Lin, Jing; Du, Jing; Li, Qiaoli; et al.
Abstract: STUDY QUESTION: Can any new genetic factors responsible for early embryonic arrest in infertile patients be identified, together with the mechanism of pathogenic variants? SUMMARY ANSWER: We identified three homozygous variants in the F-box protein 43 gene ( FBXO43 ) in infertile patients and studies on the effects of the variants in HEK293T cells and mouse oocytes provided evidence for a causal relation between FBXO43 and female infertility. WHAT IS KNOWN ALREADY: FBXO43, an inhibitor of the anaphase-promoting complex/cyclosome, mediates Metaphase II arrest as a component of the cytostatic factor in oocytes. Both male and female Fbxo43 knockout mice are viable but sterile. FBXO43, therefore, appears to be an essential component of the mammalian cell-cycle machinery that regulates both male and female meiosis. Until now, only one article has reported a homozygous FBXO43 variant associated with teratozoospermia, but the causal relationship was not established with functional evidence. STUDY DESIGN, SIZE, DURATION: Whole-exome sequencing (WES) and homozygosity mapping were performed in 24 probands from consanguineous families who suffered from early embryonic arrest, and two different homozygous variants in FBXO43 were identified in two independent families. WES data from a further 950 infertile women with early embryonic arrest were screened for homozygous and compound heterozygous variants in FBXO43, and a third individual with an additional homozygous variant in FBXO43 was identified. The infertile patients presenting with early embryonic arrest were recruited from August 2016 to May 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: The women diagnosed with primary infertility were recruited from the reproduction centers of local hospitals. Genomic DNA samples from the affected individuals, their family members, and healthy controls were extracted from peripheral blood. The FBXO43 variants were identified using WES, homozygosity mapping, in silico analysis, and variant screening. All of the variants were confirmed by Sanger sequencing, and the effects of the variants were investigated in human embryonic kidney (HEK) 293T cells by western blotting and in mouse oocytes by complementary RNA injection. MAIN RESULTS AND THE ROLE OF CHANCE: We identified three homozygous variants in FBXO43 (NM_001029860.4)—namely, c.1490_1497dup (p.(Glu500Serfs*2)), c.1747C>T (p.(Gln583*)), and c.154delG (p.(Asp52Thrfs*30))—in three independent families. All of the homozygous variants reduced the protein level of FBXO43 and reduced the level of its downstream target Cyclin B1 in HEK293T cells. In addition, the variants reduced the ability of exogenous human FBXO43 to rescue the parthenogenetic activation phenotype in Fbxo43 knockdown mouse oocytes. LIMITATIONS, REASONS FOR CAUTION: Owing to the lack of in vivo data from the oocytes of patients, the exact molecular mechanism remains unknown and should be further investigated using knock out or knock in mice. WIDER IMPLICATIONS OF THE FINDINGS: Our study has identified three pathogenic variants in FBXO43 that are involved in human early embryonic arrest. These findings contribute to our understanding of the role of FBXO43 in human early embryonic development and provide a new genetic marker for female infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Key Research and Development Program of China (2018YFC1003800, 2017YFC1001500, and 2016YFC1000600), the National Natural Science Foundation of China (81725006, 81822019, 81771581, 81971450, 81971382, and 82001552), the project supported by the Shanghai Municipal Science and Technology Major Project (2017SHZDZX01), the Project of the Shanghai Municipal Science and Technology Commission (19JC1411001), the Natural Science Foundation of Shanghai (19ZR1444500), the Shuguang Program of the Shanghai Education Development Foundation and the Shanghai Municipal Education Commission (18SG03), the Foundation of the Shanghai Health and Family Planning Commission (20154Y0162), the Capacity Building Planning Program for Shanghai Women and Children's Health Service, and the collaborative innovation center project construction for Shanghai Women and Children's Health. None of the authors have any competing interests. TRIAL REGISTRATION NUMBER: N/A